2017
DOI: 10.1073/pnas.1620133114
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial ESX-1 secretion system mediates host cell lysis through bacterium contact-dependent gross membrane disruptions

Abstract: Mycobacterium tuberculosis and Mycobacterium marinum are thought to exert virulence, in part, through their ability to lyse host cell membranes. The type VII secretion system ESX-1 [6-kDa early secretory antigenic target (ESAT-6) secretion system 1] is required for both virulence and host cell membrane lysis. Both activities are attributed to the pore-forming activity of the ESX-1-secreted substrate ESAT-6 because multiple studies have reported that recombinant ESAT-6 lyses eukaryotic membranes. We too find ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
280
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(289 citation statements)
references
References 77 publications
7
280
1
1
Order By: Relevance
“…Although EsxA appears to be insufficient to promote ESX-1-mediated membrane lysis, the study by Conrad et al definitively showed that the M. marinum ESX-1 system functions to lyse membranes in a contact-dependent manner (182). Contact-dependent membrane lysis by mycobacteria has been suggested but not directly demonstrated in several earlier studies (44,167,184).…”
Section: Esx-1 a Membranolytic Systemmentioning
confidence: 98%
See 2 more Smart Citations
“…Although EsxA appears to be insufficient to promote ESX-1-mediated membrane lysis, the study by Conrad et al definitively showed that the M. marinum ESX-1 system functions to lyse membranes in a contact-dependent manner (182). Contact-dependent membrane lysis by mycobacteria has been suggested but not directly demonstrated in several earlier studies (44,167,184).…”
Section: Esx-1 a Membranolytic Systemmentioning
confidence: 98%
“…Conrad et al found undeniably that EsxA is not sufficient to promote membrane lysis (182). Recombinant EsxA is widely acquired directly from the BEI repository or produced using a nondenaturing protocol, which includes the addition of detergent (183).…”
Section: Esx-1 a Membranolytic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…ESX-1 allows cytosolic contact and mediates vacuoles rupture [47]; the protein intervenes in host cell lysis in a contact dependent way, producing gross membrane disruptions [48]. DNA transfer through conjugation is also a function of ESX-1 system [49]; a phenomenon called "distributive conjugal transfer" that describes a genetic exchange between recipient and donor is dependent of ESX-1 in M. smegmatis [50].…”
Section: Esx-1mentioning
confidence: 99%
“…NOX2 is a multiprotein enzyme complex that assembles and activated in response to phagocytosis. This enzyme complex transfers electrons across the membrane from cytosolic NADPH to molecular oxygen, the reaction produce superoxide anions (O 2 − ) which dismutates into hydrogen peroxide (H 2 O 2 ) and generates toxic hydroxyl radicals [48]. iNOS is induced upon IFN-γ activation and produces nitrite and nitrate via nitric oxide (NO), this reacts with O 2 − and forms peroxynitrite (OONO − ) [97].…”
Section: Resistance To Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 99%